Making fuller use of survey data. - Phillipson, Michael; Political and Economic Planning (London, P.E.P., 1968)
This report deals with three complementary groups of problems that any archive has to face. First, there are problems of archive's external relations and particularly those concerned with the acquisition of data; the second group comprises those which are internal to the archive ; the third is concerned directly with the ways in which assimilated data can be used to develop secondary analysis
"A PEP report."
Bibliographical footnotes.
osc 11/03/2019
Loans
Keywords: Information storage and retrieval systems; Social sciences; Social surveys